A Contention-Based Routing Protocol for VANET - Deling Huang; Yusong Yan (Universitas Ahmad Dahlan, 2016)
In VANETs, vehicles as nodes are self-organized and inter-communicated without centralized authority. The topology formed by vehicles changes quickly, which makes routing become instability. Position-based routing, compared with traditional routing, is more scalable and feasible. Thus it has been proven stabler for VANETs than conventional routing. However, the frequently changed topology and nodes density could break the path a packet is following. Thus designing a robust multi-hop routing in VANET is challenging. This paper proposes an enhanced position-based routing protocol called CBGR, which takes into account the velocity and direction of vehicles in VANET. Simulation results show that CBGR achieves a high level of routing performance in terms of hop counts, network latency and packet delivery ratio both in dense or sparse vehicular ad-hoc networks.